Manual therapy for temporomandibular disorder in older adults: an integrative literature review - Laiza de Oliveira Lucena; Camila Maria Mendes Nascimento; Nadja Maria Jorge Asano; Maria das Graças Wanderley de Sales Coriolano; Carla Cabral dos Santos Accioly Lins (Revista CEFAC, 2022)
ABSTRACT Purpose: to describe the manual therapy techniques used to treat the temporomandibular disorder in older adults. Methods: an integrative literature review assessing scientific publications indexed in six databases: MEDLINE/PubMed, Web of Science, CINAHL, Scopus, LILACS, and PEDro. Only intervention studies were included, with no restriction of date or language. The articles included in the review were assessed with the Critical Appraisal Skills Programme. Results: after consulting the databases, 88 articles were found, six of which were considered eligible. No study was found exclusively approaching older adults. According to the analysis of the risk of bias, two articles were classified as low-risk, two as intermediate, and two as high-risk. The manual therapy techniques were intra- and extraoral massage, temporomandibular joint and cervical spine mobilization, myofascial release, trigger-point finger pressure, and deep transverse massage. Conclusion: the studies observed improved mandibular movements and masticatory function, eased pain, and reduced anxiety.